PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR), CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN KONSUMEN MEMBELI PRODUK HINO DI PT. INDOMOBIL PRIMA NIAGA MEDAN - WILLIAM PARLINDUNGAN SIHOMBING (LP2MTBM MAKARIOZ, 2020)
The purpose of this study was to determine the effect of Corporate Social Responsibility, brand image and price onconsumers' decision to buy Hino products at PT. INDOMOBIL PRIMA NIAGA Medan. The population in this study were Hinobuyers at PT. INDOMOBIL PRIMA NIAGA Medan in 2018 with 34 people in total. The samples taken were 34 people whowere saturated samples because the population was less than 100. The technique of collecting data using questionnaires. ntesting the hypothesis it can be concluded that: (1) there is an influence between X1 to Y of tcount = 21,185, (2) there is aninfluence between X2 to Y of tcount = 17,825 (3) there is an influence between X3 to Y of tcount = 9,453 and (4) there is aninfluence between X1,X2,X3 simultaneously to Y of Fcount = 534,161. Test results of determination, the effect of X1, X2, X3simultaneously on Y is 98.2% and the rest is influenced by other factors. Based on the results of the study, it was suggestedto PT. PRIMA NIAGA INDOMOBIL Medan so that : (1) The company publishes and disseminates information on the ethicsof the company's operations and business to consumers, so that consumers know that the company has social responsibilityand consumers do not see the company as seeking profit only in doing business.. (2) Increase the variety of colors owned byHino products, in order to maintain the consumer's purchase intention to PT. Medan PRIMA NIAGA INDOMOBIL did notdecline and did not cause boredom towards the products that the company offered to consumers and this would maintain theproduct's brand image. (3) Prices offered on Hino products must match the results used. This keeps consumers from beingdisappointed when using it.